Genitourinary imaging cases - Casalino, David A. 4 0 16; (William Arthur) Waickus, Cynthia M.;Schwer, William A.;Plantz, Scott H.; 5 (New York McGraw-Hill, 2010)
The chapters presented parallel the core content areas included on the Family Medicine Certification/Recertification Examination. Every attempt has been made to include the most accurate, current information. Nonetheless, medicine is a dynamic field. The half-life of medical information continues to decline, while the addition of new information is exploding at an exponential rate. In this text, we have attempted to condense complex concepts into basic principles. The intent of the text is to maximize your test scores, not to serve as reference source for information--Provided by publisher.
Machine generated contents note: 1. Cardiovascular -- 2. Pulmonary -- 3. Gastrointestinal -- 4. Metabolic and Endocrine -- 5. Neurology -- 6. Clinical Pharmacology and Toxicology -- 7. Infectious Disease -- 8. Rheumatology, Immunology, and Allergy -- 9. Genitourinary -- 10. Environmental -- 11. Hematology and Oncology -- 12. Dermatology -- 13. Obstetrics and Gynecology -- 14. Surgery: General and Trauma -- 15. Ophthalmology -- 16. Ear, Nose, Throat -- 17. Orthopedics -- 18. Sports Medicine -- 19. Pediatrics -- 20. Geriatrics -- 21. Psychology -- 22. Imaging -- 23. Preventative Medicine and Epidemiology.
Rev. ed. of: Family practice board review / [editor-in-chief] William A. Schwer ; [associate editors] Scott H. Plantz, Gillian Emblad. 3rd ed. c2006.
Includes bibliographical references (p. 567-575)
Keywords: 2 -- 0; 6; Family medicine;Family Practice -- 20 -- Examinations, questions, etc.;Examination Questions; 20; 2